How does the method of farmland transfer affect the “non-grain” of farmland in China? - Wang, Hanrui; Zhao, Qingjun (Frontiers in Sustainable Food Systems, 2024)
Introduction The phenomenon of “non-grain” of farmland poses a major threat to food security. Currently, there is still debate about the relationship between farmland transfer and the “non-grain” of farmland. Currently, there is no consensus on the relationship between farmland transfer and the non-grain use of farmland. This article focuses on the evolution of farmland transfer methods, examines the impact of farmland transfer methods on the non-grain use of farmland, and highlights the importance of effectively promoting farmland transfer, curbing the non-grain use of farmland, and ensuring food security. Methods Based on the China Rural Revitalization Survey (CRRS) data, this paper uses probit and ivprobit models to estimate the causal relationship between farmland transfer methods and the “non-grain” of farmland. Grouped regressions are conducted from three dimensions of geographical environment, village governance, and economic development to test the heterogeneity of the impact of farmland transfer methods. Finally, the pathways of action are analyzed from the perspectives of farmers’ identity transformation and contract signing. Results The organized transfer can significantly reduce the degree of “non-grain” of farmland, and its effect is stronger when the village party secretary has a higher level of education and also serves as the village head. This effect is mainly manifested through increasing the probability of farmers becoming new agricultural operators, joining cooperatives, signing formal contracts, and determining the lease term. Discussion The policy implications of this study emphasize that to curb the “non-grain” of farmland and ensure food security, it is important not only to increase the rate of farmland transfer but also to promote the organization of farmland transfer transactions. This includes facilitating the transfer of farmland from inefficient smallholders and cultivating new agricultural operators. Simultaneously, leveraging the supervisory and management role of village collectives can encourage farmers to sign more formal written contracts, clarify the purpose of farmland transfer, and supervise and manage the use of farmland during the subsequent contract execution stage. A limitation of this study is that it relies on cross-sectional data and does not observe the time variation of farmland transfer methods for the same farmers or their long-term impact on the “non-grain” of farmland.